Ethnomedicinal Plants Used by Tribals of Raniganj Coalfield Area of West Bengal - Saha, Amit (Indian Forester, 2014)
An ethnobotanical survey was carried out in Raniganj coalfield area of Burdwan district, West Bengal during the year 2010-2011. The investigations revealed that the region sustains a very rich medicinal plant wealth. The uses of plants, plant parts have been discussed. The study revealed that some plant species show preferential use in the tribal medicine in the study area.